2008
DOI: 10.1002/ajpa.20798
|View full text |Cite
|
Sign up to set email alerts
|

Grandmothers' longevity negatively affects daughters' fertility

Abstract: The evolution of postmenopausal longevity in human females has been the subject of debate. Specifically, there is disagreement about whether the evolution of the trait should be understood as an adaptive or a neutral process, and if the former, what the selective mechanism is. There are two main adaptive proposals to explain the evolution of postreproductive longevity: the grandmother and the mother hypotheses. The grandmother hypothesis proposes that postreproductive longevity evolved because it is selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…It implies a trade-off between rearing existing, still altricial children and giving birth to a new one. The second is the mother hypothesis, which states that a post-fertile grandmother can help her fertile daughter [17]. They found that neither of these ideas alone is sufficient to explain the evolution of menopause under a realistic range of life-history parameters; however, a combined model can explain it [16, 18].…”
Section: Introductionmentioning
confidence: 99%
“…It implies a trade-off between rearing existing, still altricial children and giving birth to a new one. The second is the mother hypothesis, which states that a post-fertile grandmother can help her fertile daughter [17]. They found that neither of these ideas alone is sufficient to explain the evolution of menopause under a realistic range of life-history parameters; however, a combined model can explain it [16, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The only way to ensure that isolates are not cryptically structured is through geneaological reconstruction. 6,7 In general, however, reconstructed pedigrees tend to span very few generations, and hence one has to resort to indirect evidence about structuring, typically obtained through analyses of genetic variation. To our knowledge, there has been no empirical comparison of genealogically and genetically inferred relationships in isolated populations.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses conducted on data that were collected to test this hypothesis have yielded equivocal results (Hill and Hurtado, 1991, 1996; Peccei, 1995, 2001; Alvarez, 2000; Lahdenperä et al, 2004; Kuhle, 2007; Madrigal and Meléndez-Obando, 2008; Hawkes et al, 2011; Kachel et al, 2011). Grandmothers in contemporary hunter-gatherer societies (e.g., Aché) typically gain through kin selection only approximately 5% an additional offspring (Hawkes et al, 1998).…”
Section: Changes and Hypothesesmentioning
confidence: 99%
“…Grandmothers in contemporary hunter-gatherer societies (e.g., Aché) typically gain through kin selection only approximately 5% an additional offspring (Hawkes et al, 1998). Researchers also have tested whether menopause, itself, is adaptive and found that, in premodern European (e.g., Finnish) societies, grandmothers gained 2 additional grandchildren per decade past age 50 years (Lahdenperä et al, 2004); in other premodern (e.g., Costa Rican) societies, in contrast, longer lifespan was associated with fewer grandchildren (Madrigal and Meléndez-Obando, 2008). No research has demonstrated genetic accounting consistent with inclusive fitness gains expected through kin selection to compensate for lost individual fitness.…”
Section: Changes and Hypothesesmentioning
confidence: 99%